(3GdebGeGJ GdMQjQjIs - (3GdbGSe Hf Ydj Hf eMeO Hf YKeGf, CHh eMeO GdMQjQj GdHUQj,J (B516 (3g` s ((3GdeOQSI GdYeGOjI s)
(3ChdgG (B:s
(3hHYO, aEfg LQi HHYV CfOjI GdCOH GdPj QcOJ aj gPG GdYUQ QjMg s
(3BNQgG (B:s
(3hcGfJ gPg NGJeI GdJdGbj bGd GdTjN CHheMeO GdbGSe Hf Ydj, gPG BNQ GdebGeGJ s
(3fSNI NGeSIs
(3HgG GhQGb HNW eZGjQs
(3HghGeTgG hHjf GdSWhQ MhGT cKjQI ddfGSN hHgG WeS ef HYO JQbjYs
(3hHBNQgG bQGAI SfI (B1103(3g```` s
(3hQO CjVkG JMJ Qbe (B2186 (3COH s
(3bQf GdfSN (B:s
Keywords: (3GdCOHs